A case report on overlap syndrome: diagnostic and management challenges - Jibin Simon; Saranya C.; Indhumati E.; Ananthakumar P.K.; Manoj Sivasamy; Sharan Bose (Romanian Journal of Rheumatology)
Overlap syndromes are inflammatory rheumatic conditions in which patients show clinical manifestations suggestive of multiple distinct immune diseases. This case report discusses a complex instance involving Sjögren’s disease, rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE) in a woman in her 30s. Lupus nephritis, a severe kidney inflammation associated with SLE, and diffuse alveolar hemorrhage (DAH), a life-threatening lung complication characterized by bleeding into the alveolar spaces, further complicated her clinical course. Initially presenting with acute lower limb pain, swelling, and rash, suggesting systemic involvement beyond RA, laboratory findings of hypocomplementemia and renal involvement raised suspicion of SLE. The subsequent development of polyserositis, mesenteric vasculitis, and DAH underscored the complexity of her condition. This case highlights the importance of a holistic approach that integrates clinical expertise, advanced diagnostics, and tailored therapeutic interventions to optimize patient outcomes. Early recognition and prompt management of complications are crucial in mitigating morbidity and improving prognosis, emphasizing the need for vigilant monitoring and interdisciplinary collaboration in the management of connective tissue diseases.